Access to data and reports after completion of a research project - Nagy, Murielle (Études/Inuit/Studies, 2011)
During research projects, ethical protocols must be followed to ensure protection of the rights and intellectual property of Aboriginal peoples and researchers. In such a context, researchers collect and analyse data, write reports, present their findings at conferences, and publish them. Once the project is completed, what are the researchers’ rights to the data they have collected and the reports they have written? What are their duties? These questions are particularly relevant to those researchers who work with or for Aboriginal organisations. Before signing any contract or research agreement, researchers should make a point of retaining the right to use the data and reports for their own writing and publishing.We are beginning to realise the obvious: a story does not exist as something to be captured but as something to be passed on (Morrow and Schneider 1995: 2).